Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.cmet.2013.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Human CIA2A-FAM96A and CIA2B-FAM96B Integrate Iron Homeostasis and Maturation of Different Subsets of Cytosolic-Nuclear Iron-Sulfur Proteins

Abstract: SUMMARY Numerous cytosolic and nuclear proteins involved in metabolism, DNA maintenance, protein translation, or iron homeostasis depend on iron-sulfur (Fe/S) cofactors, yet their assembly is poorly defined. Here, we identify and characterize human CIA2A (FAM96A), CIA2B (FAM96B), and CIA1 (CIAO1) as components of the cytosolic Fe/S protein assembly (CIA) machinery. CIA1 associates with either CIA2A or CIA2B and the CIA targeting factor MMS19. The CIA2B-CIA1-MMS19 complex binds to and facilitates assembly of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
174
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(196 citation statements)
references
References 47 publications
12
174
1
Order By: Relevance
“…The Fbxw2 gene encodes an F-box and WD-40 domain protein and has been shown to positively regulate ubiquitination of hGCM1, a zinc-containing transcription factor involved in placental and parathyroid development (70,71). The protein encoded by Eepd1 is known to interact with CIA1 (cytosolic iron-sulfur protein assembly component 1) and potentially contribute to the maturation of Fe/S proteins (72). These genes are involved in different biological processes, showing the complexity of molecular mechanisms underlying obesity.…”
Section: Methodsmentioning
confidence: 99%
“…The Fbxw2 gene encodes an F-box and WD-40 domain protein and has been shown to positively regulate ubiquitination of hGCM1, a zinc-containing transcription factor involved in placental and parathyroid development (70,71). The protein encoded by Eepd1 is known to interact with CIA1 (cytosolic iron-sulfur protein assembly component 1) and potentially contribute to the maturation of Fe/S proteins (72). These genes are involved in different biological processes, showing the complexity of molecular mechanisms underlying obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Numbers of independent TAP experiments in which the proteins were copurified with C terminally or N terminally TAP-tagged GRXS17 as bait in each system are presented. Interactions that were confirmed in yeast (Tarassov et al, 2008;Li et al, 2009;Zhang et al, 2011), in humans (Rual et al, 2005;Stehling et al, 2012Stehling et al, , 2013Rolland et al, 2014), or in Arabidopsis (this study; Arabidopsis Interactome Mapping, 2011; Couturier et al, 2014;Duan et al, 2015) are shown in bold. GSrh, GSrhino; Nd, Not determined; *, peptides retrieved cannot discriminate between CTU1 and CTU1L.…”
Section: Grxs17 Associates With the Cia Complex And Fe-s Proteinsmentioning
confidence: 99%
“…15 Stehling et al 14 showed that FAM96A is involved in metabolism, DNA maintenance, and protein translation, facilitating the effective induction of cell death via the mitochondrial apoptosis pathway by binding pro-apoptotic Apaf-1 protein, yet it is poorly expressed in most of tumor cells. FAM96A, as a pro-apoptotic tumor suppressor, presented therapeutic effects for tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] FAM96A was described as a novel pro-apoptotic tumor suppressor and has therapeutic effects in gastrointestinal stromal tumors in vitro and in vivo. 17 In addition, the expression of FAM96A was decreased in HCC cells.…”
Section: Introductionmentioning
confidence: 99%